Biochemical thermodynamics : applications of Mathematica - Alberty, Robert A. 4 0 16; 5 (Hoboken, N.J. : Wiley-Interscience, 2006)
Accompanying CD-ROM contains the full text, as well as macros that help scientists and engineers solve their particular problems.
Includes bibliographical references and index.
System requirements for for accompanying CD-ROM: Mathematica 5.1 or higher.
Keywords: 2 -- 0; 6; Mathematica (Computer file);Mathematica (Computer file); Mathematics. -- Thermodynamics;Physical biochemistry.;Bioenergetics.;Energy Metabolism.;Thermodynamics. -- 20; 20; 2